PENGARUH LATIHAN KELINCAHAN DAN KOORDINASI TERHADAP KEMAMPUAN SPIKE KLUB BOLA VOLI MERAK JAYA - Putra, Novrianto Tri; Binsar Hasudungan Sihombing; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of agility training and coordination training on the spike ability of Merak Jaya Volleyball Club players and to examine the differences in the effects of the two training methods. This research employed an experimental method using a Two-Group Pretest–Posttest Design. The sample consisted of 30 athletes who were divided into two groups: Group A received agility training, while Group B received coordination training. The research instrument was a spike ability test. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Paired Sample t-Test, and the Independent Sample t-Test with the assistance of SPSS version 22. The results showed that agility training had a significant effect on spike ability, with a significance value of 0.000 (< 0.05) and an increase in the mean score from 15.20 to 21.33, representing an improvement of 6.13 points. Coordination training also had a significant effect on spike ability, with a significance value of 0.000 (< 0.05) and an increase in the mean score from 16.13 to 20.53, representing an improvement of 4.40 points. Furthermore, the Independent Sample t-Test yielded a significance value of 0.383 (> 0.05), indicating that there was no statistically significant difference between the effects of agility training and coordination training on the spike ability of the players. Based on the findings, it can be concluded that both agility training and coordination training are effective in improving the spike ability of Merak Jaya Volleyball Club players. Although agility training demonstrated a greater mean improvement than coordination training, the difference was not statistically significant.